The Influence of perceived benefits and barriers to digital adoption among small and medium enterprises (SMES) in Manila, Philippines - Anunciacion, Alxzandyr Kvorgx E. Pascua, James Andrei. Regacho, Ma. margarita M. Tagle, Eral John D. 4 0 16; 5
u
Business Research : (BSBA major in Operations Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2